Inhibiting Factors in the Implementation of Pre and Post Nursing Conferences - Hasna Tunny; Siti Rochmaedah; Yerry Soumokil (Sarana Ilmu Indonesia (salnesia), 2026)
The professionalism of nurses was reflected from how nurses communicate with each other. One form of communication carried out by nurses is the nursing conference. This aimed to discuss the patient's condition, which can produce effective strategies and hone critical thinking skills to plan activities in subsequent nursing services for sustainability. In reality, the implementation of nursing conferences is not carried out well. This was due to a lack of direction, lack of nurse knowledge and high workload. The purpose of this study was to analyze the relationship between factors affecting nursing conferences in providing nursing care. The research method used a descriptive correlation with cross-sectional approach. 102 nurses were sampled. Data analysis used the chi-square test. The results obtained were a relationship between nurses' knowledge (p-value < 0.001) and directing function (p-value < 0.001) with obstacles to the implementation nursing conferences. There was no relationship between nurses' workload and obstacles to the implementation of pre- and post-nursing conferences (p-value = 0.185). It can be concluded that there is a relationship between nurses' knowledge and directive function and barriers to implementing nursing conferences. There is no relationship between nurses' workload and barriers to implementing nursing conferences.